An architecture for adhesive mobile crowdsourcing application - Aris H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Adhesives; Costs; Ubiquitous computing; Critical success factor; Household expenditure; Mobile crowdsourcing; Sources of informations; Crowdsourcing